Kashmir : The Burning of a Paradise - Edited & Compiled Khayal, Ghulam Nabi (Srinagar, Kashmir Kashmiri Writers Conference, 1992)
Compilation of news articles on the human rights violations in the Kashmir Valley during the armed insurgency since 1990.
Include Illustration
Keywords: India--Jammu and Kashmir -- Politics and government -- Human rights